Strategi Guru Aqidah Akhlak dalam Peningkatan Akhlakul Karimah Siswa di MI Gabungan Usaha Perbankan Pendididkan Islam (Guppi) Laban, Mojolaban, Sukoharjo Tahun Ajaran 2021/ 2022 - Tutik Oktavia Sari; Nur Hidayah; Heri Gunawan (MODELING: Jurnal Program Studi PGMI, 2022)
This research is a qualitative research by taking the background of the place in MI Gabungan Usaha Perbankan Pendidikan Islam (GUPPI) Laban by using the habituation method in the learning proscess. Data was collected by means of in depth interviews, research observations, and documentation. While the data analysis steps user are data collection, datareduction, data processing and analysis, and the last is data conclusion. The results showed that: 1) The strategy of Aqidah Akhalak teachers at the (GUPPI) Laban MI had implemented student discipline behavior in improving morality. 2) the inhibiting factors that affect the improvement of Akhlakul Karimah at MI GUPPI Laban include the first, the lack of supervision of parents/ guardians of students, the second is environmental factors, the third is from the teachers themselves because there are some teachers who are not professional (teachers). Whose diploma is not in sync with the subject being taught), and fourthly the media used by the teacher is inadequate if the teacher cannot keep up with technological developments, learning will become monotonous. While the supporting factors that influence the improvement of Akhlakul Karimah at MI GUPPI Laban are the first quality of teachers in managing the class so that the class becomes conducive and effective and the second is about the facilities provided by the teacher to students.